Introns: the “dark matter” of the eukaryotic genome - Girardini, Kaitlin N.; Olthof, Anouk M.; Kanadia, Rahul N. (Frontiers in Genetics, 2023)
The emergence of introns was a significant evolutionary leap that is a major distinguishing feature between prokaryotic and eukaryotic genomes. While historically introns were regarded merely as the sequences that are removed to produce spliced transcripts encoding functional products, increasingly data suggests that introns play important roles in the regulation of gene expression. Here, we use an intron-centric lens to review the role of introns in eukaryotic gene expression. First, we focus on intron architecture and how it may influence mechanisms of splicing. Second, we focus on the implications of spliceosomal snRNAs and their variants on intron splicing. Finally, we discuss how the presence of introns and the need to splice them influences transcription regulation. Despite the abundance of introns in the eukaryotic genome and their emerging role regulating gene expression, a lot remains unexplored. Therefore, here we refer to introns as the “dark matter” of the eukaryotic genome and discuss some of the outstanding questions in the field.